Predictive factors of treatment outcomes for hospital care in children with acute methadone poisoning - Yasamin Atighi; Nastaran Eizadi-Mood; Marjan Mansourian; Amin Zamani; Ali Saffaei; Ali Mohammad Sabzghabaee (Wolters Kluwer Medknow Publications, 2018)
Objective: The trend of methadone toxicity in children and adolescents seems to be increasing in Iran since it is used as a legal measure of the treatment for opioids addiction in methadone maintenance therapy clinics. In the present study, we describe the clinical and demographical characteristics of acute methadone toxicity in a cohort of pediatric poisoned patients in Isfahan, Iran and discussed the predictive factors for their treatment outcomes. Methods: In this 4-year cross-sectional study which was performed from 2013 to 2016 in a referral university hospital (Isfahan, Iran), medical records of the demographic and admission time clinical characteristics of all in-patients aged <18 years with acute methadone poisoning were abstracted and analyzed. According to the outcomes of hospital care and treatment, patients were divided as survived without medical complication and patients survived with at least one medical complication or death. Findings: A total number of 157 (79 male) children and adolescents with a mean age of 105.4 ± 6.1 months were hospitalized and included in the study. A total of 145 (92.4%) patients survived and discharged from the hospital without any medical complication. Pupil size, respiratory rate, and level of consciousness were predictive factors for the outcome of death or medical complications. Conclusion: It seems that methadone poisoning in children and adolescents is more commonly accidental in school-aged boys (6-12 years old) and it occurs mostly with the syrup dosage form, especially when one of the parents or people who live with the child has an addiction history and if the patients' house located in lower socioeconomic class area of Isfahan city (Iran).